Study on the mechanical and optical properties of kraft liner paper produced from mixing of OCC and virgin hardwoods kraft pulp - Ali Khalili gasht rodkhani (Regional Information Center for Science and Technology (RICeST), 2009)
This study was aimed to investigate the effects of mixing OCC fibers with mixed hardwoods kraft pulp at Iran Wood and Paper Industry Co (Chuka). OCC has been repulped according to the common method in paper recycling industry and its freeness, along with that of virgin kraft pulp, were measured. The pulps were beaten to reach the required freeness values to make kraft liner paper, and have been then mixed at 10/90, 20/80, 30/70, 50/50 and 70/30 percentage rates of OCC and virgin kraft pulp, respectively. Handsheets were made from each composition and their mechanical and optical properties have been measured, according to required standard test methods, and compared with those of the control (100% virgin kraft pulp), using ANOVA method. Grouping of the mean values was done by Duncan test and normalization equation was computed to determine the best treatment. The results indicate decreasing the values of tensile, tear and burst, folding endurance and density in comparison with those of the control (100% virgin kraft pulp), but bulk, thickness and opacity have been increased. The score belonging to each treatment show to produce paper possessing proper mechanical and optical properties using OCC fibers, the allowed proportion of these fibers is 50 percent.